2017
DOI: 10.1016/j.carbpol.2017.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds and twist in cellulose microfibrils

Abstract: There is increasing experimental and computational evidence that cellulose microfibrils can exist in a stable twisted form. In this study, atomistic molecular dynamics (MD) simulations are performed to investigate the importance of intrachain hydrogen bonds on the twist in cellulose microfibrils. We systematically enforce or block the formation of these intrachain hydrogen bonds by either constraining dihedral angles or manipulating charges. For the majority of simulations a consistent right handed twist is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 30 publications
4
37
2
Order By: Relevance
“…For any angular velocity condition, the shear modulus at the temperature less than 300 K is always smaller than that at 10 K. The value of shear modulus obtained here is about 1.4 GPa at 10 K, and about 0.8 -1.0 GPa between 100 and 300 K. They are somewhat smaller than the experimental value, 1.8 -3.8 GPa [15]. The calculated value reported for CMF using MD with the all atom model is 1.6 GPa [16]. This slight discrepancy is caused by inhomogeneous deformation of the whole system due to the influence of the fixed and velocity-constrained ends.…”
Section: Torsional Simulation Of Single Cmfcontrasting
confidence: 57%
See 1 more Smart Citation
“…For any angular velocity condition, the shear modulus at the temperature less than 300 K is always smaller than that at 10 K. The value of shear modulus obtained here is about 1.4 GPa at 10 K, and about 0.8 -1.0 GPa between 100 and 300 K. They are somewhat smaller than the experimental value, 1.8 -3.8 GPa [15]. The calculated value reported for CMF using MD with the all atom model is 1.6 GPa [16]. This slight discrepancy is caused by inhomogeneous deformation of the whole system due to the influence of the fixed and velocity-constrained ends.…”
Section: Torsional Simulation Of Single Cmfcontrasting
confidence: 57%
“…It is reported that CNF's experimental shear modulus is between 1.8 and 3.8 GPa [14], and the simulated one by all-atom model is 1.6 GPa [15]. Although knowledge on tensile properties of CMF is increasing, the material's behavior in torsion or bending deformation is quite different [13] [16]. In addition, the actual CMF is tangled complicatedly to form a hierarchical structure.…”
Section: Introductionmentioning
confidence: 99%
“…As the relative change of L 004 with moisture content was of similar magnitude in all samples (Table 3), an increase in the twisting with drying appears a more plausible explanation. Based on molecular dynamics simulations, the twist rate of CMFs and their bundles, and thereby also the longitudinal coherence length, can be affected for instance by the fibril dimensions (Kannam et al 2017) or interactions with water (Paajanen et al 2019). However, it is not clear if the systems simulated so far are sufficiently representative of the complex, multicomponent structure of the native wood cell wall.…”
Section: :2åmentioning
confidence: 99%
“…Several molecular-level mechanisms have been proposed as the driving force behind the twisting of single microfibrils. Since the phenomenon was first observed in classical MD simulations (Yui et al 2006;Matthews et al 2006;Yui and Hayashi 2007), it has been attributed, solely or in part, to (1) changes in intra and interlayer hydrogen bonding patterns (Paavilainen et al 2011) (2) attractive, interlayer, van der Waals forces (Hadden et al 2013) (3) torsional forces due to the geometry of the trans-glycosidic hydrogen bonds, especially the HO2-O6' bond (Bu et al 2015;Conley et al 2016), and (4) a joint effect of several mechanisms (Kannam et al 2017). In a related discussion (Zhao et al 2013), it has been speculated that amorphous regions repeating along the length of the fibril would be needed to release stresses involved with the twist, and to keep the cellulose I b structure intact.…”
Section: Introductionmentioning
confidence: 99%